Childhood experiences and personal traits as predictors of reliance on science and on religion to make sense of the world: results of a national US study - Park, Crystal L. (Religion, brain & behavior, 2025)
People often rely on two distinct worldviews, religion and science, to make sense of the world, and the degree to which they rely on each holds profound implications for their lives. However, the precursors shaping these different sense-making approaches remain poorly understood. The present study examined the extent to which individuals’ recollected childhood religion- and science-related experiences, along with personal traits, were associated with their present reliance on these ways of making sense. A cross-sectional online survey was conducted with a representative sample of U.S. adults. Multivariate regression modeling simultaneously assessed predictors of reliance on religion (RoR) and reliance on science (RoS) after controlling for age, gender, income and education. Among retrospective childhood predictors, greater religious credibility-enhancing displays by caregivers predicted current higher RoR and lower RoS. Opportunities for science learning during childhood predicted increased RoS but were not significantly associated with RoR. Among current measures of personal traits, higher levels of agreeableness predicted both RoR and RoS. Distinct associations were also found: authoritarianism predicted only RoR, while openness and (inversely) extraversion predicted RoS. This study enhances our understanding of the complex interplay between childhood experiences, personal traits, and reliance on religion and science in adulthood.